An Evaluation Of Postgraduate School-Based Teacher Education Program In Malaysia - Tan , Cheng Im (2011)

(untitled)
The primary purpose of this study was to evaluate the strengths and weaknesses of the postgraduate SBTE program as an alternative route in training teachers. The post graduate SBTE was conducted by using modules through self-directed learning and tutorials, with the collaboration of the school mentor teachers. To bridge the gap between theory and practice, this study applied a mixed-method in theory-driven-evaluation which was developed by Chen (1990). The samples for questionnaire were 100 Teachers-in- Training (TiTs), 100 mentor teachers, and 48 tutors.